Effect of Gallium as an Additive Over Corresponding Ni–Mo/γ-Al2O3 Catalysts on the Hydrodesulfurization Performance of 4,6-DMDBT - Huang, Meng; Huang, Wenbin; Li, Anqi; Yang, Han; Jia, Yijing; Yu, Zhiqing; Xu, Zhusong; Wang, Xiaohan; Zhou, Yasong; Wei, Qiang (Frontiers in Chemistry, 2022)
Experiments were carried to research the different contents of Ga2O3 modification effects on the hydrodesulfurization (HDS) performance of 4,6-DMDBT catalyzed by stepwise impregnation method. Characterization techniques such as XRD, BET, HRTEM, NH3-TPD, Py-FTIR were performed to determine the effects of each modification of catalyst by Ga on the properties of the prepared supports and catalysts. The Characterization results indicated that the introduction of Ga2O3 with appropriate content (2 wt.%) promoted Ni and Mo species to disperse uniformly and more Ni atoms doping into the MoS2 crystals, which also increased the average stacking number and the length of MoS2. As a result, the more NiMoS active phases were favored to form in the system. The specific surface area and the amounts of acid sites were increased facilitating the adsorption of reactant molecules and the hydrodesulfurization reactions. The hydrodesulfurization (HDS) results also suggested the effects of Ga-modification play a very important role in the catalytic performance of the corresponding catalysts. The catalyst Ga-Ni-Mo/Al2O3 exhibited the highest conversion rate towards 4,6-DMDBT HDS when the amount of Ga2O3 loading was 2 wt.% with LHSV of 2.5 h-1 at 290 ℃ and Ga modification also can effectively improve the DDS route selectivity in varying degrees.